PENGARUH KUALITAS SUMBER DAYA MANUSIA DAN MANAJEMEN PENGELOLAAN TERHADAP PENGHIMPUNAN INFAQ DAN SEDEKAH PADA BADAN AMIL ZAKAT NASIONAL (BAZNAS) KOTA JAMBI TAHUN 2016-2022 - Putri, RTS Nadia Rosanti; Habriyanto, Habriyanto; Prasaja, Ahmad Syukron (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2023)
The influence of the quality of human resources and management on the collection of infaq and alms at the national amil zakat (BAZNAS) Jambi City in 2016-2022. There are many strategies that can be done to attract people's interest to donate and give charity in BAZNAS, one of which is the quality of human resources in BAZNAS itself. The quality of human resources greatly determines the interest of the community in providing infaq and alms to BAZNAS. Apart from that, the management of infaq and alms fund management at BAZNAS must also be well organized. This study aims to determine whether the quality of human resources and management have an effect on the collection of infaq and alms at the national zakat charity (BAZNAS) Jambi City in 2016- 2022. This study uses quantitative methods by obtaining primary data from questionnaires by taking 20 respondents. The results of the t-test show that the variables of human resource quality and management have a significant effect. The results of the F-test stated that the quality of human resources and management had a significant effect on the collection of infaq and alms. The value of the coefficient of determination of the quality of human resources and management is 33.2% for the collection of infaq and alms.